Information literacy capabilities of upper secondary students: the case of Vietnam. Issue 6 (2nd September 2019) - Ngo, Huyen Thi; Pickard, Alison Jane; Walton, Geoff
Abstract : Purpose: This paper aims to focus on investigating information literacy (IL) capabilities and IL self-assessment of Vietnam's upper secondary students. Design/methodology/approach: The investigation was conducted in two upper secondary schools in the country using a multiple-choice questionnaire. The questionnaire was based on the IL competency-level assessment toolkit of high schools in the USA, the tool for real-time assessment of IL, to measure students' IL in terms of developing search strategies, evaluating information sources, using information ethically and using English to engage with information effectively. Findings: The findings reveal that students' IL has not been well equipped. There is a real need to work toward improving the IL capability of Vietnam's upper secondary students. The findings also reveal gender differences in IL capabilities. Research limitations/implications: The research used a closed-response questionnaire, which is considered appropriate to engage with Vietnamese high-school students, to explore students' lower-level IL skills and their self-assessment rather than higher-level thinking competencies. Practical implications: This research may help Vietnam's educators understand high-school students' IL competency and raise their awareness of the importance of IL to encourage the implementation of an IL programme. Originality/value: This study contributes to the existing knowledge by adding substantially to current understanding of IL level of Vietnamese upper secondary students – a context which has not been explored to date. It also indicates gender inequality in IL capabilities.